Transcultural approaches to the concept of imperial rule in the Middle Ages - Scholl, Christian, 1981-; Gebhardt, Torben R.; Clauss, Jan, 1982- (Peter Lang Edition, 2017)
The volume examines imperial rule in the Middle Ages. It asks for the characteristics of imperial leadership as well as the reasons why some rulers strove for imperial titles such as emperor whereas others voluntarily shrank from them. Thus, the authors adopt a transcultural perspective, covering Europe, Byzantium and the Islamic Middle East.